Oxidative Stress and Lipid Peroxidation – A Lipid Metabolism Dysfunction - Borza, Claudia; Muntean, Danina; Dehelean, Cristina; Săvoiu, Germaine; Şerban, Corina; Simu, Georgeta; Andoni, Mihaiela; Butur, Marius; Drăgan, Simona (IntechOpen, 2013)
None